Critical contribution of Na+‐Ca2+ exchanger to the Ca2+‐mediated vasodilation activated in endothelial cells of resistance arteries. Issue 4 (5th January 2018) - Lillo, Mauricio A.; Gaete, Pablo S.; Puebla, Mariela; Ardiles, Nicolás M.; Poblete, Inés; Becerra, Alvaro; Simon, Felipe; Figueroa, Xavier F.
Abstract : Na + ‐Ca 2+ exchanger (NCX) contributes to control the intracellular free Ca 2+ concentration ([Ca 2 +]i ), but the functional activation of NCX reverse mode (NCXrm) in endothelial cells is controversial. We evaluated the participation of NCXrm‐mediated Ca 2+ uptake in the endothelium‐dependent vasodilation of rat isolated mesenteric arterial beds. In phenylephrine‐contracted mesenteries, the acetylcholine (ACh)‐induced vasodilation was abolished by treatment with the NCXrm blockers SEA0400, KB‐R7943, or SN‐6. Consistent with that, the ACh‐induced hyperpolarization observed in primary cultures of mesenteric endothelial cells and in smooth muscle of isolated mesenteric resistance arteries was attenuated by KB‐R7943 and SEA0400, respectively. In addition, both blockers abolished the NO production activated by ACh in intact mesenteric arteries. In contrast, the inhibition of NCXrm did not affect the vasodilator responses induced by the Ca 2+ ionophore, ionomycin, and the NO donor, S‐nitroso‐ N ‐acetylpenicillamine. Furthermore, SEA0400, KB‐R7943, and a small interference RNA directed against NCX1 blunted the increase in [Ca 2+ ]i induced by ACh or ATP in cultured endothelial cells. The analysis by proximity ligation assay showed that the NO‐synthesizing enzyme, eNOS, and NCX1 were associated in endothelial cell caveolae of intact mesenteric resistance arteries. These results indicate that the activation of NCXrm has a central role in Ca 2+ ‐mediated vasodilation initiated by ACh in endothelial cells of resistance arteries.— Lillo, M. A., Gaete, P. S., Puebla, M., Ardiles, N. M., Poblete, I., Becerra, A., Simon, F., Figueroa, X. F. Critical contribution of Na+‐Ca2+ exchanger to the Ca2+‐mediated vasodilation activated in endothelial cells of resistance arteries. FASEB J. 32, 2137–2147 (2018). www.fasebj.org